2017
DOI: 10.1002/jcp.25969
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast role in osteoarthritis pathogenesis

Abstract: Even if osteoarthritis pathogenesis is still poorly understood, numerous evidences suggest that osteoblasts dysregulation plays a key role in osteoarthritis pathogenesis. An abnormal expression of OPG and RANKL has been described in osteoarthritis osteoblasts, which is responsible for abnormal bone remodeling and decreased mineralization. Alterations in genes expression are involved in dysregulation of osteoblast function, bone remodeling, and mineralization, leading to osteoarthritis development. Moreover, os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 80 publications
4
93
0
1
Order By: Relevance
“…43 Several studies have suggested during the last few years that an osteoblast-like mechanism is responsible for pathological calcifications found in blood vessels and cartilage, and for those related to cancer. 3,22,23 Interestingly, MVs have been described for the pathological calcifications associated with e.g. ostheoarthritis, atherosclerosis, arteriosclerosis and tumors.…”
Section: Nano-calcifications Share Similarities With the Transient MImentioning
confidence: 99%
See 1 more Smart Citation
“…43 Several studies have suggested during the last few years that an osteoblast-like mechanism is responsible for pathological calcifications found in blood vessels and cartilage, and for those related to cancer. 3,22,23 Interestingly, MVs have been described for the pathological calcifications associated with e.g. ostheoarthritis, atherosclerosis, arteriosclerosis and tumors.…”
Section: Nano-calcifications Share Similarities With the Transient MImentioning
confidence: 99%
“…Interestingly, some of these calcifications present similarities to the structures reported in 6 physiological bone 17,21 or pathological biominerals. 3,22,23 Our study provides information for understanding the physico-chemical processes involved in the formation of pathological calcifications. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60…”
mentioning
confidence: 94%
“…Advanced OA can involve the entire joint tissue such as synovium, cartilage and subchondral bone, among that, the destruction of cartilage tissues is an important process in the pathogenesis of OA, and is the main feature of pathological changes of OA [35,36]. Further, unbalanced metabolism and synthesis of cartilage tissues can lead to cartilage wear, matrix loss and chondrocyte death in the course of OA [37].…”
Section: Discussionmentioning
confidence: 99%
“…Присутність остеобластів («low osteoarthritic osteoblasts») із низькою «артрозною» імунологічною активністю (підвищена експресія RANKL на фоні пригнічення рівня OPG, PGE 2 , IL-6 на ранніх стадіях розвитку захворювання) пов'язують із посиленням резорбції кісткової тканини та формуванням зон зниженої мінеральної щільності. Наявність остеобластів із високою «артрозною» імунологічною активністю («high osteoarthritic osteoblasts») та посиленою індукцією рівня OPG, PGE 2 та IL-6 пов'язують із підвищенням кісткоутворення, тобто формуванням ділянок склерозу [36].…”
Section: результати та їх обговоренняunclassified